ANALISIS NILAI-NILAI PENDIDIKAN KARAKTER DALAM NOVEL SULAMAN TANGAN TUHAN KARYA AMALIAH CHOTIB - Ndruru, Ida Lestari (FAGURU: Jurnal Ilmiah Mahasiswa Keguruan, 2025)
This research is motivated by uniqueness, namely that the novel Sulaman Hands of God is a literary work that is very interesting and contains the reader's curiosity, contains character education values ​​that can be taken up by the reader. This study is able to provide benefits for the reader, to be grateful for what God has given, and to understand the meaning of friendship because a friend is a place where we share happiness. The aim of this research is to describe the values ​​of character education in the novel Embroidery of God's Hands by Amaliah Chotib. This research uses a qualitative approach with descriptive methods. As a result of the research, the researcher found 8 types of character education values ​​contained in the novel Sulaman Hands of God by Amaliah Chotib, namely 13 religious values, 2 honesty values, 4 tolerance values, 7 curiosity values, 5 friendly/communicative values, 5 There are 2 love of peace, 6 social care values, 2 responsibility values, and in total there are 41 quotes. The conclusion in this research is that this novel has many character values. The more dominant character education values ​​are religious values ​​with 13 quotes and there are 10 types of character education values ​​which are not found in this novel because they tend to discuss values ​​relating to life in friendship. This novel is a serious type of novel because it invites readers to understand, absorb, reflect more seriously, and take away the learning or wisdom contained in it. Suggestions, to teachers, it is best to use the novel Sulaiman Gan's Hand by Amaliah Chotib because it contains character education values ​​that can be taken as learning for students and to prepare themselves to become teachers who have knowledge about literature. And for future researchers, as reference material for conducting relevant research.